Genetic linkage analyses redefine the roles of PfCRT and PfMDR1 in drug accumulation and susceptibility in Plasmodium falciparum - Sanchez, Cecilia P.; Mayer, Sybille; Nurhasanah, Astutiati; Stein, Wilfred D.; Lanzer, Michael (Molecular microbiology, 2011)
Resistance to quinoline antimalarial drugs has emerged in different parts of the world and involves sets of discrete mutational changes in pfcrt and pfmdr1 in the human malaria parasite Plasmodium falciparum. To better understand how the different polymorphic haplotypes of pfmdr1 and pfcrt contribute to drug resistance, we have conducted a linkage analysis in the F1 progeny of a genetic cross where we assess both the susceptibility and the amount of accumulation of chloroquine, amodiaquine, quinine and quinidine. Our data show that the different pfcrt and pfmdr1 haplotypes confer drug-specific responses which, depending on the drug, may affect drug accumulation or susceptibility or both. These findings suggest that PfCRT and PfMDR1 are carriers of antimalarial drugs, but that the interaction with a drug interferes with the carriers' natural transport function such that they are now themselves targets of these drugs. How well a mutant PfCRT and PfMDR1 type copes with its competing transport functions is determined by its specific sets of amino acid substitutions.
Gesehen am 04.10.2022